Weathering the storm: best practices for nonprofits in crisis. Issue 4 (12th September 2014) - Kinsky, Emily S.; Drumheller, Kristina; Gerlich, R. Nicholas; Waters, Richard D.
<x xml:space="preserve">Abstract</x> Nonprofit organizations are as susceptible to crisis as any organization as exemplified by Livestrong's attempts to outlive Lance Armstrong's downfall and Planned Parenthood (PP) overcoming Susan G. Komen for the Cure's (SGK) policy to defund organizations under investigation. The public battles held on social media during crises such as these have forced organizations onto new battlegrounds. Supporters for each of these nonprofits proudly shared their thoughts via tweets (e.g. #IstandwithPP) and status updates, as the organizations raced to control the situation. PP had tweeted SGK's policy change creating a bevy of support while sending SGK into a reversal that is still costing racers. Surveys were distributed following Armstrong's performance‐enhancing drug use confession and SGK's funding policy announcement to determine attitudes toward giving after organizational crisis. The Theory of Planned Behavior (TPB) was used to assess the strength of attitude, social norms, and perceived behavioral control on the intent to donate to these organizations. The use of TPB expands nonprofit marketing horizons by helping better understand stakeholder intentions and their causes. On the basis of the findings, best practices for nonprofits handling crisis were identified. In particular, organizations need to know their target audiences, know what will make supporters remain, look at crises as opportunities for renewal, be honest, and apologize when appropriate. Copyright © 2014 John Wiley & Sons, Ltd.